(untitled) (Nigerian Journal of Physiological Sciences, 2024)
Diabetes problems are more likely to occur in people with low vitamin D levels. In this study, Sudanese individuals diagnosed with type 2 diabetes mellitus (T2DM) had their serum glucose, HbA1c, vitamin D, and inflammatory markers assessed. Thirty men and thirty women who had been diagnosed with T2DM for at least two years were among the 120 participants of both sexes, ages 35 to 69, who were enrolled in this case-control study. As a control group, the second group consisted of sixty healthy individuals (30 men and 30 women). Every participant had a thorough medical history taken, with special attention to the length of their diabetes, its medical history, and any previous problems. During the clinical examination and laboratory tests, the following criteria were evaluated: total WBC, ESR, CRP, HbA1c, and serum vitamin D3. When 25(OH) vitamin D3 levels were utilized to assess T2DM patients, they showed significantly lower mean blood concentrations than controls: 23 (38.3%) had vitamin D insufficiency, 23 (38.3%) had vitamin D deficiency, and 14 (23.3%) had sufficient vitamin D. Vitamin D-deficient patients had significant increases in HbA1c, glucose, CRP, and total WBC. Additionally, when comparing the mean ESR values of diabetes patients to those of the control group, there is a statistically significant rise. ESR did not significantly alter depending on the controlling level. Males also had a numerically higher level of vitamin D3 than females. Compared to healthy normal controls, individuals with type 2 diabetes have noticeably reduced vitamin D3 levels. Furthermore, in T2DM patients, there was a connection between elevated inflammatory markers and HbA1c and insufficiency in vitamin D.